Cystoscopy Simulation for Obstetrics and Gynecology Residents: Commercially-Developed Compared With Low-Cost Cystoscopy Trainers [62]. (May 2015) - Elmer, Caroline Grace; Book, Nicole; Wade, Angie
Abstract : OBJECTIVE: To evaluate the utility of a commercially-developed cystoscopy trainer in teaching basic cystoscopy knowledge and technique to novice residents. A secondary analysis then compared the educational benefits of this new trainer with those of a "home-made" model that cost 15. METHODS: Study participants included obstetrics and gynecology residents at Riverside Methodist Hospital and Doctors West Hospital in Columbus, Ohio. Residents completed a pretest, received formal instruction and practice in cystoscopy with a commercially-developed trainer, and completed a posttest. The testing and instruction were the same as those used in a previous study performed at our institution using a low-cost trainer. Results with the new trainer then were compared with results from the low-cost trainer. RESULTS: Seven postgraduate year (PGY)-1 residents, three PGY-2 residents, two PGY-3 residents, and three PGY-4 residents (n=15) participated in the study. The majority of residents reported a "novice" skill level (n=11) in cystoscopy; the remaining residents (n=4) reported a "moderate skill" level. None indicated prior formal training with cystoscopy. A paired t -test showed significant improvement between pretest and posttest scores using the new, commercially-developed trainer ( P ⩽.001). Pretest scores from the commercially-developed trainer and the low-cost trainer were compared, showing no statistical difference ( P =.459). The same analysis was performed for posttest outcomes and again showed no statistical difference ( P =.250). Overall improvement in pretest to posttest scores was not statistically different ( P =.222). CONCLUSION: Simulation training for cystoscopy significantly improves basic understanding of cystoscopy in residents. However, there appears to be no difference in effectiveness of training between a commercially-developed cystoscopy trainer and a low-cost model.